Variation in seedling root traits in wild barley (Hordeum vulgare L. ssp. spontaneum) germplasm. (16th July 2014) - Tyagi, Kuldeep; Lee, Hyo Jeong; Lee, Chong Ae; Steffenson, Brian J.; Kim, Young Jin; Yun, Song Joong
Abstract : Improved root architecture of cultivated barley can improve crop performance in drought-prone areas. In this study, seedlings of 315 wild barley ( Hordeum vulgare subsp. spontaneum ) accessions from the Wild Barley Diversity Collection (WBDC) were grown under hydroponic conditions for 8 d after germination and then root characteristics were analysed. Significant differences were observed among the accessions with regard to seminal root number (SRN), root length (RL), specific root length (SRL), root fresh weight and root dry weight (RDW). Principal component analysis explained about 81% of the total variation for ten traits. Principal component (PC) 1, PC2 and PC3 explained about 38, 30 and 13% of the total variation among the accessions. The two most prominent contributors in each PC were RL and SRL, RDW and SRN, and the longitude and latitude of the collection sites, respectively. Accessions WBDC266, WBDC302, WBDC286 and WBDC011 had the longest RL and the highest RDW, specific dry root weight and SRL, respectively. These accessions may be useful genetic resources for the improvement of these root traits in cultivated barley.